On ψ-Caputo Fractional Nonlinear Volterra-Fredholm Integro-Differential Equations - Sharif, Abdulrahman A.; Hamoud, Ahmed A. (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, we establish some new conditions for the existence and uniqueness of solutions for a class of nonlinear ψ-Caputo fractional Volterra-Fredholm integro-differential equations with boundary conditions. The desired results are proved by using Banach and Schaefer’s fixed point theorems in Banach spaces. Furthermore, Ulam’s type stability of the proposed problem is studied.